Phases of the Recovery Process From Psychiatric Disabilities - Spaniol, LeRoy (International Journal of Psychosocial Rehabilitation, 2013)
The purpose of this paper is to describe the phases of recovery from psychiatric disabilities and their implica - tions for interventions. The paper identifies the many variables at work in recovery, including phases that oc - cur over time, areas of development within which people change, developmental tasks and processes, and turn - ing points that represent important shifts within the phases and within the developmental dimensions.